(untitled) (Publicaciones en Ciencias y Tecnología, 2011)
Proca equations foresee the possibility of a nonzero photon mass. In this context of electrodynamics of finite range, the approaches used to determine the mass of the photon, or its upper limits, are traditionally based on classical methods. In this paper, we present a brief overview of the latest experimental methods that are based on a quantum approach. It is shown that quantum approaches can compete and even surpass traditional methods.